Students and recorded lectures: survey on current use and demands for higher education - Pierre Gorissen; Jan van Bruggen; Wim Jochems (Association for Learning Technology, 2012)
Online recordings of lectures provide students with anytime-anyplace access to lectures. Research shows that students prefer courses accompanied by online recordings and an increasing number of universities provide recorded lectures. This paper presents the results of a study into the use of recorded lectures at two universities in the Netherlands. The goal of the study is to gain a better understanding of the way that this group of students use recorded lectures. This understanding will enable the creation of usage scenarios that need to be supported. Our results show that students use recorded lectures as a replacement for missed lectures and for study tasks, like preparing for an exam. A large proportion of the students report that they watch 75–100% of a recorded lecture when the view one. The fact that students did not mention the quality of the actual lectures appears not to influence the use of the recorded lectures. Recorded lectures for courses that only use the blackboard are viewed less often. There are also interesting differences in the use of recorded lectures of the different groups of students at the two universities. To increase the credibility and validity of the results, we need a more direct way to measure the use of recorded lectures by students. Methodological triangulation using the log data for the recorded lectures can provide this.